Atheroma of the facial artery mimicking a parotid gland tumor: A case report. Issue 46 (November 2016) - Lee, Dong Hoon; Yoon, Tae Mi; Lee, Joon Kyoo; Lim, Sang Chul
Abstract: Introduction: Atheroma of the facial artery is an extremely rare disease. Clinical Findings/Patient Concerns: Herein, we report an extremely rare case of an atheroma arising from the facial artery, mimicking a parotid gland tumor. Diagnoses: The preoperative diagnosis was a right-sided parotid gland tumor. Interventions: We performed removal of the right parotid gland tumor, via a modified face-lift incision. Outcomes: Histological examination of the specimen revealed an atheroma of the facial artery. Conclusion: Clinicians should consider atheroma in the differential diagnosis of tumors arising around the parotid gland.